POSITIVE PERSONALITY TRAIT IN KAHLIL GIBRAN’S THE BROKEN WINGS - Dea Jesikha; Purwarno Purwarno; M. Manugeren (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
The objectives of the research are to identify positive personality traits in the poetical novella of The Broken Wings and to expose some actions, thoughts and feelings of the major characters that could be categorized into positive personality traits. Some related theories on personality traits are applied in this research, one of which, is the one  proposed by Lauther (2012) stating that personality traits appear in the forms of action, attitude and behavior some may be positive  such as: love, friendship, respect,  honesty, responsibility, adaptability, compatibility, resolution, compassion, patience, courage and loyalty; while some others negative  such attitude as laziness, shyness, arrogance, closeness , dishonesty, cruelty, and intolerance.  The research is conducted by means of qualitative descriptive method proposed by Kothari (2004) having a goal of a comprehensive summarization, in everyday terms, of specific events experienced by individuals or groups of individuals. The research results show that there are four significant positive personality traits found in the whole course of the story: Love, Friendship, Resolution and Respect and these traits are all experienced by the major characters.